Evidence of sea level drawdown at the end of the Messinian salinity crisis and seismic investigation of the Nahr Menashe unit in the northern Levant Basin, offshore Lebanon - Kartveit, Kyrre Heldal; Ulsund, Heidrun Breiset; Johansen, Ståle Emil (Basin research, 2019)
Several important aspects of the Messinian salinity crisis (MSC) are still subject to controversy and debate after more than 40 years of studies. Recent work from the eastern Mediterranean have provided a renewed stratigraphic framework for the basin that is inconsistent with previous interpretation studies in the area. This study presents a description of the evolution of the depositional environment in the northern Levant Basin in a time interval surrounding the end of the famous event, from Late Messinian to the Pliocene. Through seismic mapping, we have identified a sediment package overlying the intra‐Messinian truncation surface (IMTS). This package is interpreted as an axial fluvial system running along the Levant Margin in stage 3 of the salinity crisis, likely composed of redeposited evaporites and clastic material. The system was fed primarily from a large fan system building out from the basin margin during a time of sea‐level low stand following a major erosional event, and presumably also from similar systems along the Latakia Ridge and Syria. Our interpretation also lends weight to the theory of a subaerial origin for the truncation surface after a catastrophic desiccation event succeeding the deposition of the halite‐dominated Messinian evaporite succession, based on differences in maximum erosional depth throughout the basin. After the deposition of the post‐IMTS package, deep marine settings were restored in the basin, and hemipelagic sediments from the Nile Delta and the Levant Margin have dominated the sediment deposition since.